Box-jumping Training with Adding Weights and Auxiliary Tools and Its Effect on the Achievement Ability of the Legs and Accuracy Shoot from Jumping to the Zone Area for Advanced Basketball Players - Ahmed Abdul-Imam Kazem Muhammad al-Saadi (Indian Journal of Forensic Medicine & Toxicology, 2021)
Box-jumping exercises, which are considered a type of plyometric training, are one of the training methodsthat can be used in a wide field to develop muscular capacity and strength distinguished by speed (accordingto the type and requirements of the activity) and which has to do with the development of the achievementability of various sports, including the game of basketball, which is a series of interconnected technical skillsthat the player needs in high coordination and compatibility, as the basketball player, in order to obtain goodtechnical performance, must have the basic physical elements and high skill performance, and he must useall the muscles and joints of the body working on movement accurately. It is high and smooth because ithelps to collect the force produced from all the muscles from the bottom of the foot to other parts. The aimof the research is to prepare box-jumping exercises from different heights and distances, and this is donewith weights added to the trunk, arms and legs once, and again with tools that help in the performance ofjumping from the boxes and this will be determined according to the amounts of work-ability and accordingto the goal of each exercise, and to identify the effect of these exercises to developing achievement ability ofthe legs and shoot accuracy from jumping to the zone for advanced basketball players. The aforementionedexercises were applied for a period of two months at the rate of three training units per week on the researchsample. They are the players of Al-Tadamon Sports Club participating in the Elite Advanced League, thenumber of which is 12 players. In a random way, they were divided into two equal groups.